PROSEDUR PENGUJIAN SUBSTANTIF AKUN KAS DAN SETARA KAS PT XYZ OLEH KANTOR AKUNTAN PUBLIK PKF HADIWINATA - Putri Muthia Sari, (2022)
PT XYZ is engaged in construction services. The author has the opportunity to audit cash accounts and cash equivalents for PT XYZ's annual financial statements, several types of cash owned by PT XYZ such as general cash, cash in banks, petty cash and cash equivalents. Cash and Cash Equivalents are assets that are liquid in nature and every company transaction is related to cash and cash equivalents, so the balance of the cash account so as not to have the potential for misappropriation and misuse. so that the purpose of conducting an examination of the financial statements of cash accounts and cash equivalents is to assess the reasonableness that has been presented in the financial statements that have been carried out by an independent auditor. With the creation of this report, it aims to find out that cash and cash equivalents examinations using the vouching and cash-taking methods at PT XYZ by KAP PKF Hadiwinata have been carried out in accordance with generally accepted audit standards in Indonesia.